On the crack formation of non–dendritic structure deformed in the semi–solid state. (4th August 2014) - Chen, C.P.; Tsao, C.–Y.A.
The fact that specimens show cracking at the semi–solid temperature where the ductility of the solid phase should have been very high is due to the presence of both solid and liquid phases and to the non–dendritic nature of the specimens. The degree of cracking is smaller for higher semi– solid deformation temperatures, because at these temperatures there is more liquid phase to 'glue' together the solid phase. The solid–liquid segregation phenomenon is less significant for higher deformation rates, since the liquid phase has less time to respond to the deformation to flow laterally towards the edge. The degree of cracking is smaller for lower semi–solid deformation rates, as the liquid phase, due to the solid–liquid segregation, can fill more completely the crevices formed. There is a sudden increase in the degree of cracking as the deformation temperature increases across the solidus temperature, due to the presence of both solid and liquid phases and to the non–dendritic nature of the specimens. Immediately below the solidus temperature, the degree of cracking is much lower than that immediately above the solidus. Although the deformation behaviours are similar for both solid and semi–solid deformation, the main causes for these deformation behaviours are entirely different from each other. The crack formation is less severe for dendritic structures than it is for non–dendritic structures during the semi–solid deformation due to the solid dendritic network of the former.